Minimally Invasive Methods for Staging in Lung Cancer: Systematic Review and Meta-Analysis - Labarca, Gonzalo; Aravena, Carlos; Ortega, Francisco; Arenas, Alex; Majid, Adnan; Folch, Erik; Mehta, Hiren J.; Jantz, Michael A.; Fernandez-Bussy, Sebastian (Pulmonary Medicine, 2016)
Introduction. Endobronchial ultrasound (EBUS) is a procedure that provides access to the mediastinal staging; however, EBUS cannot be used to stage all of the nodes in the mediastinum. In these cases, endoscopic ultrasound (EUS) is used for complete staging. Objective. To provide a synthesis of the evidence on the diagnostic performance of EBUS + EUS in patients undergoing mediastinal staging. Methods. Systematic review and meta-analysis to evaluate the diagnostic yield of EBUS + EUS compared with surgical staging. Two researchers performed the literature search, quality assessments, data extractions, and analyses. We produced a meta-analysis including sensitivity, specificity, and likelihood ratio analysis. Results. Twelve primary studies (1515 patients) were included; two were randomized controlled trials (RCTs) and ten were prospective trials. The pooled sensitivity for combined EBUS + EUS was 87% (CI 84–89%) and the specificity was 99% (CI 98–100%). For EBUS + EUS performed with a single bronchoscope group, the sensitivity improved to 88% (CI 83.1–91.4%) and specificity improved to 100% (CI 99-100%). Conclusion. EBUS + EUS is a highly accurate and safe procedure. The combined procedure should be considered in selected patients with lymphadenopathy noted at stations that are not traditionally accessible with conventional EBUS.